Principle Guided Investing: The Use of Exclusionary Screens and Its Implications for Green Investors - Urs von Arx (Swiss Journal of Economics and Statistics, 2007)
This paper examines how "green" investors can induce firms to invest in clean production technology. The 1-period model incorporates heterogeneous agents - Markowitz investors and green investors – and two groups of firms working either with clean or polluting technology. Since green investors apply exclusionary environmental screens, some firms will invest in abatement technology in order to switch to a clean technology and thereby raising firm value. The number of firms working with clean technology will be larger, the higher the proportion of green investors, the lower costs of abatement technology, the higher diversification benefits of stocks of clean firms and if positive spill-overs for clean firms exist.
Keywords: G10; Q5; 330; Socially Responsible Investment; Pension Funds